Characterization of mouse cytomegalovirus MHC-1 homologs - Mans, Janet (My University, 2009)
Mouse cytomegalovirus (MCMV), a β-herpesvirus, encodes the m145 family of glycoproteins. Several members of this family are predicted to adopt the MHC-I fold although their amino acid sequences exhibit less than 30% identity to classical MHC-I (MHC-Ia) proteins. Our aim was to determine how related the viral proteins are to MHCIa and characterize them in terms of cellular expression, structure and function. We studied the cellular localization of FLAG-tagged m17, M37, m145, m151, m152, m153 and m155 in transfected mouse fibroblasts. Flow cytometry analysis of transfected cells showed that M37, m145, m151 and m153 localize predominantly to the cell surface, whereas the majority of m17, m152 and m155 remain inside the cell. MHC-Ia proteins require assembly with β2-microglobulin (β2m) and peptide for stable cell surface expression. Transient transfection studies with β2m- or transporter associated with antigen (TAP)-deficient cell lines revealed that M37, m145, m151 and m153 could be expressed stably at the cell surface in the absence of β2m or TAP expression. To generate protein material for crystallization screening we evaluated both bacterial and insect cell expression systems. Although most m145 family members could be expressed in bacteria in insoluble inclusion bodies, none of the proteins could be accurately refolded. Since M37, m151 and m153 are cell surface molecules with the potential to bind receptors on host cells, we focused our structure determination efforts on them and evaluated their expression in Drosophila S2 insect cells. The extracellular domains of all three proteins expressed at significant levels, however, m151 tended to aggregate and precipitate over time. M37 and m153 were stable and could easily be purified to homogeneity. Size exclusion chromatography and SDS-PAGE analysis of m153 suggested that it forms a non-covalent homodimer. Analytical ultracentrifugation experiments confirmed this observation and provided an estimated molecular mass of 78.8 kDa. Enzymatic and mass spectrometry analyses showed that insect-expressed m153 is highly glycosylated. We tested a wide range of crystallization conditions for m153. It formed very fragile crystals and after optimization we obtained several that diffracted to 2.3 Å. To determine the structure of m153, we prepared a seleno-methionine derivative in insect cells, collected data on a single crystal and solved the phases by the single anomalous dispersion method. The m153 model was refined at 2.4 Å resolution to final Rcryst and Rfree of 23% and 27.9%, respectively. The m153 homodimer is formed by two MHC-I-like heavy chains, each consisting of two α-helices arranged on a platform of seven β-strands and an Ig-like α3 domain. The monomers are arranged “head-to-tail”, with the α1α2 platform domain of one chain interacting with the Ig-like α3 domain of the other. The α1 and α2 helices are closely juxtaposed and do not form a peptide binding groove. Three N-linked carbohydrate residues were visualized in the crystal structure. Major deviations from the MHC-I fold include an extended N-terminus, which originates next to the α3 domain, and an elongated α2 helix (designated H2b) that reaches down towards the α3 domain. In addition, m153 has two unique disulfide bonds, one between strands of the platform domain and another that links the extended N-terminus to the H2b helix. Both unique disulfide bonds were verified by mass spectrometry. The canonical Ig-fold disulfide bond is present in the α3 domain. Alanine mutation of four amino acids involved in interface hydrogen bonds abolished m153 dimer formation, validating the dimer interface visualized in the structure. The crystal structure of m153, together with the recently reported m157 structure, confirms the MHC-I fold for the MCMV m145 family and highlights shared structural features in the m145 family. We have demonstrated dimerization of full-length m153 in mammalian cells by bimolecular fluorescence complementation and co-immunoprecipitation studies. Further, we have shown that m153 is expressed at the surface of MCMV-infected cells at early times after infection. To initiate a search for host ligands of m153, we generated a reporter cell line by introducing an m153-human zeta chain fusion protein into 43.1 cells that contain an NFAT-driven GFP construct. While a variety of mouse cell lines were unable to stimulate the m153-reporter cells, coculture with mouse splenocytes specifically induced GFP production in m153-reporters but not in the parental or control reporter cell lines. We identified conventional CD11c+ and plasmacytoid dendritic cells (DCs) as the most potent m153-reporter cell stimulating populations in the spleen. The stimulation was shown to be m153-specific, dose- and cell contact-dependent. DCs derived from bonemarrow cultures also potently stimulated the m153-reporter cells. Macrophages and NK cells exhibited weaker stimulation of the reporter cells, indicating lower levels of ligand or that only small subsets of the cells express a ligand. DCs from several mouse strains, but not from the rat, stimulated m153-reporter cells. We evaluated DC surface phenotype and migratory capacity after coculture with m153-reporter cells or on m153-coated plates, but could not detect any changes induced specifically by the presence of m153.
Keywords: mouse cytomegalovirus; MHC-1 homologs